Long-term glycemic control and factors, associated with response to pump insulin therapy in children - D. N. Laptev; A. O. Emelyanov; E D Medvedeva; S. V. Pereverzeva; V. A. Peterkova (Сахарный диабет, 2021)
Background: In recent years, pump-based insulin therapy, also known as continuous subcutaneous insulin infusion (CSII), has become a common treatment for children with type 1 diabetes mellitus (T1DM). Despite the fact that, in general, children with type 1 diabetes achieve the best glycemic control indices during pump therapy, while there is a significant heterogeneity of metabolic outcomes among individual patients, many children with CSII do not reach the target level of HbA1c.Objective: To assess the level of glycemic control and factors associated by withdrawal of use, the response to treatment with prolonged use of CSII in children with type 1 diabetes.Materials and methods: The study included 458 children aged 1 to 18 years, treated to pump therapy at least 3 years before the study, the presence of the analyzed data in the register.Results: The level of HbA1c decreased by -0.7% compared with the primary endpoint, which was accompanied by an increase in the number of patients who reached the target level of HbA1c (<7.5%) from 17% to 36%. The best response was observed for patients under 6 years of age with HbA1c over 9% for pump insulin therapy, as well as in patients who regularly use additional bolus and basal functions and CGM. The main reason for stopping the use of the insulin pump is the inconvenience of using and wearing — 47.7%. Risk factors for pump abandonment: later age of start treatment on CSII and frequent episodes of severe hypoglycemia.Conclusion: According to the results of the study, it was shown that pump therapy is an effective method of insulin therapy, which allows to achieve a lower level of HbA1c compared to the initial values.